High-Frequency Electrical Modulation of the Superior Ovarian Nerve as a Treatment of Polycystic Ovary Syndrome in the Rat - Pikov, Victor; Sridhar, Arun; Lara, Hernan E. (Frontiers in Physiology, 2018)
The polycystic ovary syndrome (PCOS) is the most prevalent ovarian pathology in women, with excessive sympathetic activity in the superior ovarian nerve (SON) playing an important role in inducing the PCOS symptoms in the rats and humans. Our previous studies have shown that surgical transection of the SON can reverse the disease progression, prompting us to explore the effect of the kilohertz alternating frequency current (KHFAC) modulation as a method of reversible non-surgical suppression of the nerve activity in the rodent model of PCOS. 56 animals were randomly allocated to 3 groups: the control group (n = 18), PCOS group (n = 15), and PCOS + KHFAC modulation group (n = 23). The physiological, anatomical, and biochemical parameters of ovarian function were evaluated during the progression of the experimentally-induced PCOS and during long-term KHFAC modulation applied for 2-3 weeks. The KHFAC modulation has been able to reverse the pathological changes in assessed PCOS parameters, namely the irregular or absent estrous cycling, formation of ovarian cysts, reduction in the number of corpora lutea, and ovarian norepinephrine concentration. The fertility capacity was similar in the PCOS and PCOS + KHFAC groups, indicating the safety of KHFAC modulation approach. In summary, these results suggest that the KHFAC modulation approach of suppressing the SON activity could become a useful treatment modality for PCOS and potentially other pathological ovarian conditions.